Pengaruh Subjective Norm serta Perceived Benefit terhadap Pemakaian E-money di Samastra Coffee Kota Klungkung - Jayanti, Ni Kadek Yumi; Irwansyah, M. Rudi (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This research aims to find out: (1) the effect of subjective norms on the use of e-money at Samastra Coffee, Klungkung City; (2) the effect of perceived benefit on the use of e-money at Samastra Coffee, Klungkung City; and (3) the effect of simultaneous subjective norm and perceived benefit on the use of e-money at Samastra Coffee, Klungkung City. The population in this research is that all consumers transact using e-money at Samastra Coffee on Jalan Srikandi II Semarapura Kangin Klungkung, totaling 90 people. The sampling technique used is incidental sampling. Data collection methods used are interviews and questionnaires. The data analysis used in this research is multiple linear regression analysis. The results of the research state that (1) there is a partial effect of subjective norm on the use of e-money at Samastra Coffee, Klungkung City; (2) there is an effect of perceived benefit on the use of e-money at Samastra Coffee, Klungkung City; and (3) there is a simultaneous influence of subjective norm and perceived benefit on the use of e-money at Samastra Coffee, Klungkung City.